2018
DOI: 10.1016/j.jaac.2018.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Objective and Quantitative Eye Tracking−Based Measures of Autism Risk and Symptom Levels

Abstract: Objective: The primary aim of this study was to develop and validate eye tracking-based measures for estimating autism spectrum disorder (ASD) risk and quantifying autism symptom levels. Method: Eye tracking data were collected from youth during an initial evaluation visit, with administrators blinded to all clinical information. Consensus diagnoses were given by the multidisciplinary team. Participants viewed a 5- minute video that included 44 dynamic stimuli from 7 distinct paradigms while gaze was recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 36 publications
2
51
0
3
Order By: Relevance
“…Indeed, a common behavioral symptom of ASD is reduced eye contact [Senju & Johnson, 2009;Tanaka & Sung, 2016], and previous eye-tracking studies have reported that children with ASD exhibit weaker gaze preferences for people [Moore et al, 2018;Pierce et al, 2016], faces [Chawarska, Macari, & Shic, 2012;Chita-Tegmark, 2016;Constantino et al, 2017;Jones, Carr, & Klin, 2008;Jones & Klin, 2013;Papagiannopoulou, Chitty, Hermens, Hickie, & Lagopoulos, 2014;Riby & Hancock, 2009;Rice, Moriuchi, Jones, & Klin, 2012;Wang, Campbell, Macari, Chawarska, & Shic, 2018], biological motion [Falck-Ytter, Rehnberg, & Bölte, 2013;Klin, Lin, Gorrindo, Ramsay, & Jones, 2009], and following the gazes of others [Bedford et al, 2012]. These studies have suggested that quantifying gaze behavior with eye tracking may be a potent technique for estimating the initial severity of social symptoms in ASD and sensitively tracking their change over time or in response to treatments [Frazier et al, 2018;Sasson & Elison, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a common behavioral symptom of ASD is reduced eye contact [Senju & Johnson, 2009;Tanaka & Sung, 2016], and previous eye-tracking studies have reported that children with ASD exhibit weaker gaze preferences for people [Moore et al, 2018;Pierce et al, 2016], faces [Chawarska, Macari, & Shic, 2012;Chita-Tegmark, 2016;Constantino et al, 2017;Jones, Carr, & Klin, 2008;Jones & Klin, 2013;Papagiannopoulou, Chitty, Hermens, Hickie, & Lagopoulos, 2014;Riby & Hancock, 2009;Rice, Moriuchi, Jones, & Klin, 2012;Wang, Campbell, Macari, Chawarska, & Shic, 2018], biological motion [Falck-Ytter, Rehnberg, & Bölte, 2013;Klin, Lin, Gorrindo, Ramsay, & Jones, 2009], and following the gazes of others [Bedford et al, 2012]. These studies have suggested that quantifying gaze behavior with eye tracking may be a potent technique for estimating the initial severity of social symptoms in ASD and sensitively tracking their change over time or in response to treatments [Frazier et al, 2018;Sasson & Elison, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…Wang, Campbell, Macari, Chawarska, & Shic, 2018), biological motion (Falck-Ytter, Rehnberg, & Bölte, 2013;Klin, Lin, Gorrindo, Ramsay, & Jones, 2009), and following the gazes of others (Bedford et al, 2012). These studies have suggested that quantifying gaze behavior with eye-tracking may be a potent technique for estimating the initial severity of social symptoms in ASD and sensitively tracking their change over time or in response to treatments (Frazier et al, 2018;Sasson & Elison, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Eye-tracking measures are increasingly proposed as sensitive biomarkers for ASD, particularly convenient to assess the core social attention deficits contributing to ASD. Remote eye gaze tracking is a noninvasive technique not requiring participants' overt responses and has not significant technical or ethical limitations (Frazier et al 2018). Furthermore, measures can be rapidly collected across a wide range of ages and probably in different cultural settings.…”
Section: Overview Of Research Directionsmentioning
confidence: 99%